Green antibacterial molecules: sophorolipids with varying fatty acid chain - Hirlekar, Swarali; Abhyankar, Isha; Kane, Kartiki; Trimukhe, Kalpana; Prabhune, Asmita; Nisal, Anuya (Trends in Biomaterials and Artificial Organs, 2021)
Antibiotic resistance is a rising problem of over the last decade making it difficult to treat infections caused by various pathogenic bacteria. To tackle this problem, newer antimicrobial strategies are being explored. Sophorolipids (SLs) are a class of biomolecules produced by a non-pathogenic yeast Starmarella bombicola (S. bombicold) with surfactant as well as potent broad spectrum antibacterial activity. In this work, we have successfully synthesized sophorolipids using different fatty acids with increasing chain length of hydrophobic tail; Lauric acid (C12)-LASL, Myristic acid (C14)-MASL, Palmitic acid (C16)-PASL and Stearic acid (C18)-SASL. We have used various techniques like FTIR, HRMS to characterize the synthesized SL. Further, we have measured properties like the critical micellar concentration for these biosurfactants and the SL's showed CMC less than or equal to 100 mg/L indicating excellent surface-active property. We have studied the antibacterial activity against gram-negative and gram-positive bacteria. Interestingly, the antibacterial activity was found to be more potent as the chain length of the fatty acid in the SL decreased. This trend was found to be reverse for toxicity towards mammalian cells. The shorter chain fatty acid SL's were found to be less cytotoxic. These results indicate that the sophorolipid candidates with shorter chain lengths would be beneficial for various biomedical applications such as tissue engineering, regenerative medicine and wound healing. Keywords: sophorolipid, biosurfactant, short chain fatty acid, antibacterial
Keywords: Antibacterial agents; Cells (Biology); Infection; Microbial drug resistance; Saturated fatty acids; Surface active agents

Myristic acid derived sophorolipid: efficient synthesis and enhanced antibacterial activity - Abhyankar, Isha; Sevi, Ganesh; Prabhune, Asmita A.; Nisal, Anuya; Bayatigeri, Santhakumari (ACS Omega, 2021)
Microbial glycolipids are one of the most interesting alternatives to chemical-based surfactants as they exhibit improved biodegradability and less toxicity. However, their potential has been limited because of specificity of the yeast toward fatty acids having a carbon 16 or carbon 18 chain. This study focuses on sophorolipid (SL) production by the yeast Starmerella bombicola using myristic acid, a medium-chain carbon-14 fatty acid that has not been used as a substrate for SL production. The production was optimized for inoculum size and lipophilic substrate concentration. Furthermore, we also studied the effect of medium-chain fatty acid on yeast cell growth and optimized the process for excellent yield. The myristic acid SL (MASL) so synthesized consisted of mono- and diacetylated forms with preferential glycosylation at the methyl end group, as determined by high-resolution mass spectrometry. Individual congeners of the crude mixture were separated using dry column chromatography and then structurally characterized by mass spectrometry. The synthesized MASL was also shown to have promising surface tension, lowering abilities with a low CMC of 14 mg/L. The SL derived from myristic acid exhibited superior antibacterial activity as compared to SL derived from oleic acid. MASL was also found to be more potent against Gram-positive organisms as compared to Gram-negative organisms. This work, therefore, demonstrates successful synthesis of myristic acid-derived SL and its superior antibacterial activity, establishing a promising future for this biosurfactant.

Bridging the gap: an investigation of biosurfactants-polymer systems - Abhyankar, Isha; Hirlekar, Swarali; Prabhune, Asmita; Nisal, Anuya (Current Opinion in Colloid & Interface Science, 2024)
Biosurfactants (BSs) have been extensively researched due to their potential applications in various fields, including textiles, cosmetics, pharmaceuticals, agriculture, and oil remediation. These BSs possess a diverse range of physical, chemical, and biological properties. In recent years, researchers have combined these biosurfactants with both natural and synthetic polymers, resulting in the development of advanced material systems that exhibit a unique combination of properties. This review focuses on highlighting the recent advancements in these biosurfactant-polymer material systems and identifies existing gaps in the literature. The combination of biosurfactants with polymers has led to the formation of interpenetrated hydrogels, films, chemically modified surfaces, vesicles, functionalized nanofiber nonwoven mats, nano-formulations, and nano-assemblies. Some studies have also investigated the interactions between biosurfactants and polymer molecules. In most cases, non-specific, non-covalent interactions, such as electrostatic interactions, hydrogen bonding, and hydrophobic interactions have been found to govern the properties of these systems. Moreover, promising results have been achieved through the covalent modification of polymer surfaces, followed by functionalization using biosurfactant molecules. The literature demonstrates that these advanced materials could find applications in various fields, including drug delivery, bioremediation, biomedical materials, and as antimicrobial agents. These findings indicate the promising potential of biosurfactant-polymer systems for future advancements in these areas.